2021
DOI: 10.3390/cancers13205035
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Molecular Diagnostics and Targeted Therapy of Myeloproliferative Neoplasms

Abstract: Somatic mutations in JAK2, calreticulin, and MPL genes drive myeloproliferative neoplasms (MPN), and recent technological advances have revealed a heterogeneous genomic landscape with additional mutations in MPN. These mainly affect genes involved in epigenetic regulation and splicing and are of diagnostic and prognostic value, predicting the risk of progression and informing decisions on therapeutic management. Thus, genetic testing has become an integral part of the current state-of-the-art laboratory work-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 110 publications
0
9
0
Order By: Relevance
“…Based on studies, JAK2 V617F mutation was seen in 95% of PV patients and about 50-60% of ET and PMF patients (12,(17)(18)(19). In this study, it was shown that the frequency of JAK2 V617F mutation was 97.1% in PV patients, 50% in ET patients, and 60.25%in PMF patients.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Based on studies, JAK2 V617F mutation was seen in 95% of PV patients and about 50-60% of ET and PMF patients (12,(17)(18)(19). In this study, it was shown that the frequency of JAK2 V617F mutation was 97.1% in PV patients, 50% in ET patients, and 60.25%in PMF patients.…”
Section: Discussionmentioning
confidence: 49%
“…Driver mutations in MPN are now formally included in the WHO diagnostic criteria for primary myelofibrosis (58 percent JAK2, 25 percent CALR and 7 percent MPL), PV (98 percent JAK2 mutational frequency), and ET (60 percent JAK2, 22 percent CALR, and 3 percent MPL mutational frequency) (10). Considering that there are genetic differences depending on the geography (11,12), and there is no study on the genetic mutation status of these diseases in the Iraqi region and especially Iraqi Kurdistan, this study aims to use molecular aspects for the diagnosis of MPN according to WHO criteria 2016 that (not only depend on morphological and clinical aspects for diagnosis) but using JAK2, CALR, MPL genes for diagnosis and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The standard treatment, particularly for PV, is therapeutic phlebotomy to achieve hematocrit <45%, sometimes combined with other therapies. Antiplatelet drugs such aspirin, and cytoreductive chemotherapy, such as, hydroxyurea (Hydrea®), α-interferon or anagrelide (Agrylin® ), are used instead of or in combination with phlebotomy for patients with a history of thrombosis to suppress the excess production of blood cells [65].…”
Section: Standard Treatmentmentioning
confidence: 99%
“…There is no single treatment option that can effectively treat all patients with MPN. The choice of treatment including the use of platelet-lowering agents, is based on risk factors including age, history of bleeding or thrombosis, vascular risk, severity of symptoms, and drug tolerance [65].…”
Section: Standard Treatmentmentioning
confidence: 99%
See 1 more Smart Citation